A Novel RAYM_RS09735/RAYM_RS09740 Two-Component Signaling System Regulates Gene Expression and Virulence in Riemerella anatipestifer - Wang, Ying; Lu, Ti; Yin, Xuehuan; Zhou, Zutao; Li, Shaowen; Liu, Mei; Hu, Sishun; Bi, Dingren; Li, Zili (Frontiers in Microbiology, 2017)
The Gram-negative bacterium Riemerella anatipestifer is an important waterfowl pathogen, causing major economic losses to the duck-producing industry. However, little is known of the virulence factors that mediate pathogenesis during R. anatipestifer infection. In this study, RAYM_RS09735 and RAYM_RS09740 were predicted to form a two-component signaling system (TCS) through bioinformatics analysis. This TCS was highly conserved across the Flavobacteriaceae. A mutant YMΔRS09735/RS09740 strain was constructed to investigate the role of the RAYM_RS09735/RAYM_RS09740 TCS in R. anatipestifer virulence and gene regulation. The median lethal dose (LD50) of YMΔRS09735/RS09740 was found to be greater than 1011 CFU, equivalent to that of avirulent bacterial strains. The bacterial abundances of the YMΔRS09735/RS09740 strain in the heart, brain, liver, blood, and spleen were significantly lower than that of the wild-type R. anatipestifer YM strain. Pathological analysis using hematoxylin and eosin staining showed that, compared to the wild-type, the mutant YMΔRS09735/RS09740 strain caused significantly less virulence in infected ducklings. RNAseq and real-time PCR analysis indicated that the RAYM_RS09735/RAYM_RS09740 TCS is a PhoP/PhoR system. This is a novel type of TCS for Gram-negative bacteria. The TCS was also found to be a global regulator of expression in R. anatipestifer, with 112 genes up-regulated and 693 genes down-regulated in the YMΔRS09735/RS09740 strain (approximately 33% genes demonstrated differential expression). In summary, we have reported the first PhoP/PhoR TCS identified in a Gram-negative bacterium and demonstrated that it is involved in virulence and gene regulation in R. anatipestifer.